Improving QoS in real-time data warehouses by using feedback control scheduling. (2018) - Hamdi, Issam; Bouazizi, Emna; Alshomrani, Saleh; Feki, Jamel
Nowadays the update frequency for traditional data warehouses cannot meet the objectives of real-time data analysis relying on data freshness. To alleviate this problem, the real-time data warehouse (RTDW) technology has emerged. A RTDW allows decision makers to access and analyse fresh data as fast as possible in order to support real-time decision processes. The RTDW must often deal with transient usage charges, due to the unpredictability of access to data. The purpose of this paper is two-fold: to maintain the behaviour of the RTDW at a stable state, as well as the reduction of the number of transactions responsible for not meeting their deadline. Moreover, we focus on optimisation techniques to speed up query processing; in particular, a query response time optimisation and storage space optimisation. This paper proposes our FCSA-RTDW architecture (feedback control scheduling architecture for RTDW) which deals with quality of service management by optimising the resources used and reducing significantly the RTDW overloads.